CORRELATION OF HYPERNATREMIA TO SUCCESS RATE OF SKIN GRAFT IN BURN PATIENTS DR. SOETOMO GENERAL ACADEMIC HOSPITAL BURN CENTER FROM 2014-2018 - Ephora Christina Wulandari; Lynda Hariani; Agus Santoso Budi (Jurnal Rekonstruksi dan Estetik)
Highlights: